What Spirituality Means for Patients and Families in Health Care - Gardner, Fiona (Journal of religion and health, 2020)
This research focuses on the spiritual care experiences of patients and families at a hospital in Australia. Twenty-four patients and 10 family members were interviewed. Results indicate the importance of relatedness: being treated as a person, reminded of your capabilities and conversations about what matters. Maintaining contact with friends and family, sustaining religious and spiritual practices, music therapy and pet therapy were also significant and contact with the natural world and shared activities. The results indicate the importance of spirituality offered through pastoral care, and that all those involved in health care can contribute to the spiritually nurturing environment that reinforces healing.